Jajar Legowo Planting System with SRI Method (System of Rice Intensification) and the Use of Planting Tools for Caplak in Simatohir Village, Padangsidimpuan District Angkola Julu - Lubis, Rafiqah Amanda; Harahap, Imelda Sari; Harahap, Qorry Hilmiyah; Permadi, Muhammad Agung; Sulaiman Abdi (Talenta Publisher Universitas Sumatera Utara, 2018)
This community service took place in Simatohir Village, Padangsidimpuan District Angkola Julu, Padangsidimpuan City. The implementation methods used are counseling methods, cultivation technique training, and mentoring. The approach method used is: a) Counseling about the application of SRI technology. b) Make demonstration plots or demonstration plots. c) Use of 2 : 1 legowo planting system using ticks. In the generative phase clearly visible results from the application of SRI are applied to the rice field cropping. There is a distance that facilitates the care of farmers, efficiency in the use of paddy water and the number of productive tillers is 25-40 tillers / clumps and the yield reaches 1337 tons with an area of ​​1000 square meters and this difference is very obvious when farmers do not use SRI , which starts from tillage which is only extracted, unbalanced fertilization, irregular irrigation, perforated plants between 10-20 plants with productive tillers only 15-23 tillers. This will have an impact on harvest yields which only reach 900 kg with an area of​​ 1000 square meters.